REVIEW ON THE PHARMACOLOGY OF THE DRUGS USED FOR COVID-19 OUTBREAK - Noor ul ain (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE:The recent global health threat is the outbreak of a viral infectious disease caused by SARS-COV2 (Severe acute respiratory syndrome-corona virus). The origin of this outbreak is from the animal market in Wuhan, China. So, it is considered as zoonotic in origin as its mode of transmission is from animals to human. This outbreak is similar to previous outbreaks of coronavirus like SARS-COV (Severe Acute Respiratory syndrome) and MERS-COV (Middle East Respiratory Syndrome). Until now different pharmacological drugs have been used to mitigate the symptoms of the COVID-19 throughout the world. There is no specific medication prescribed as the treatment of this disease. However, pharmacological drugs and immune boosting dietary therapies have been proved effective in treatment strategies.METHODOLOGY:The latest epidemiological articles, research articles, review articles, WHO guidelines and news proceedings are selected in this review. Articles were searched under the keyword search of COVID-19, drugs for COVID-19, latest COVID-19 research, surveys for covid-19. PubMed, Lancet, Elsevier, BMJ and CDC were used to accumulate the latest findings.RESULTS:There is no vaccine or other proper treatment available for this infectious disease but the symptomatic treatment is usually given to the infected person as the use of certain pharmacological as well as traditional drugs are given to reduce the symptoms associated with this disease. Furthermore, COVID-19 serious patients on ventilator are treated with the plasma therapy as with the antibiotics from the plasma of recovered patients is also in use to reduce mortality rate. CONCLUSION:To prevent this infectious disease it is important to avoid the person-to-person transmission which is mainly via coughing, sneezing, droplets of the respiration, direct contact with the infected person. So, the social distancing and self-quarantine is preferred to avoid the spread of this infectious disease. The drugs which are commonly used to reduce or eliminate the symptoms of COVID-19 are Paracetamol, Aspirin/Loprin, Dabigatran, Azithromycin, Famotidine, Ipratopium bromide, Dexamethasone,Tocilizumab, and Moxifloxacin. These drugs have been practiced by the practitioners to treat the symptoms of covid-19. However no pertinent drug has been approved as a cure of covid-19.